2017
DOI: 10.1038/nri.2017.13
|View full text |Cite
|
Sign up to set email alerts
|

New insights into mononuclear phagocyte biology from the visual system

Abstract: Major advances in mononuclear phagocyte biology have been realized, yet key questions pertinent to health and disease remain, including in the visual system. One problem concerns how dendritic cells can trigger immune responses from certain tightly regulated immune privileged sites of the eye. Another, albeit separate, problem involves whether functional specializations exist for microglia versus monocytes in neurodegenerating retinas. We examine novel insights in eye immune privilege and, separately, review r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
43
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(44 citation statements)
references
References 136 publications
1
43
0
Order By: Relevance
“…However, we cannot exclude additional retinal cell dysfunction in MPS-IIIA mice that might be due to secondary storage materials and lysosomal impairment effects. Interestingly, previous studies have shown microglia activation associated to retinal dystrophy in mouse models of MPS (Karlstetter et al, 2015;Tse et al, 2015;Kruszewski et al, 2016;Reyes et al, 2017). Therefore, we asked whether the microglia was activated in the retina of MPS-IIIA mice.…”
Section: Photoreceptor Degeneration Is Associated With Inflammation Amentioning
confidence: 94%
“…However, we cannot exclude additional retinal cell dysfunction in MPS-IIIA mice that might be due to secondary storage materials and lysosomal impairment effects. Interestingly, previous studies have shown microglia activation associated to retinal dystrophy in mouse models of MPS (Karlstetter et al, 2015;Tse et al, 2015;Kruszewski et al, 2016;Reyes et al, 2017). Therefore, we asked whether the microglia was activated in the retina of MPS-IIIA mice.…”
Section: Photoreceptor Degeneration Is Associated With Inflammation Amentioning
confidence: 94%
“…O'Koren et al () demonstrated that retinal microglia have a unique CD45(low) CD11c(low) F4/80(low) I‐A/I‐E(−) signature which is conserved in the steady state and during retinal injury. By investigating these cells, the authors found that microglia migrate to the photoreceptor outer segments while monocyte‐derived macrophages appear throughout the entire retina (Reyes et al, ). For further insights into microglia heterogeneity, the reader is directed to other excellent reviews (Hanisch, ; Reyes et al, ).…”
Section: Targeting Mononuclear Phagocytes In Retinal Degenerative Dismentioning
confidence: 99%
“…By investigating these cells, the authors found that microglia migrate to the photoreceptor outer segments while monocyte‐derived macrophages appear throughout the entire retina (Reyes et al, ). For further insights into microglia heterogeneity, the reader is directed to other excellent reviews (Hanisch, ; Reyes et al, ).…”
Section: Targeting Mononuclear Phagocytes In Retinal Degenerative Dismentioning
confidence: 99%
“…For one, it is the only barrier site that also doubles as an immune privileged tissue (Reyes et al, 2017). Immune privilege is thought to be an evolutionary adaptation that protects the delicate structures of the eye from otherwise deleterious immune responses induced by Fas/Fas ligand (Griffith et al, 1995) and other mediators (Reyes et al, 2017).…”
mentioning
confidence: 99%
“…For one, it is the only barrier site that also doubles as an immune privileged tissue (Reyes et al, 2017). Immune privilege is thought to be an evolutionary adaptation that protects the delicate structures of the eye from otherwise deleterious immune responses induced by Fas/Fas ligand (Griffith et al, 1995) and other mediators (Reyes et al, 2017). But this adaptation comes at a price, as immune privilege is also thought to also render the eye vulnerable to certain infections and tumors, which is why J. Wayne Streilein previously referred to eye immune privilege as the “Faustian Dilemma” (Streilein, 1996).…”
mentioning
confidence: 99%